Peran Pencak Silat dalam Membentuk Karakter Disiplin Siswa Thai Assa-Adah Narathiwat - Adi Nur Ali; Muhammad Bahrul Ulum Mubarok (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2025)
This study examines the role of pencak silat in shaping the character of discipline of students at Madrasah Assa-Adah, Narathiwat, Thailand, through a humanistic education perspective. Using a qualitative phenomenological method, this study involved participant observation, in-depth interviews, and document analysis. The informants in this study were 5 active students, 2 pencak silat trainers, and 3 assistant teachers. Observations were conducted for four weeks in stages. The results of the study indicate that pencak silat fosters discipline not only through structured physical training, but also through consistent reinforcement of moral values ​​such as responsibility, respect, and self-control. This training encourages students' punctuality, perseverance, and commitment, which translates into improved academic and social behavior. In addition, pencak silat fosters emotional intelligence and cooperation, providing space for self-actualization and character building in line with humanistic theory. These results confirm that pencak silat is not only a physical activity but a holistic educational tool that effectively internalizes discipline and moral development in the school environment. This study contributes to strengthening the theory of character building through non-formal education and local culture approaches. These findings indicate that pencak silat as a cultural heritage not only functions as physical exercise, but also as a natural medium to internalize values. The results of this study can be a reference for educational policies and programs in Islamic boarding schools and schools, especially in strengthening students' character education through physical-cultural activities.